UPAYA PENYULUH AGAMA DALAM MENANGGULANGI PERGAULAN BEBAS DI DESA KUTE KERING KECAMATAN BUKIT KABUPATEN BENER MERIAH - Zulkarnaen Guchi, Lina Fitri, Ramlan Padang, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
In an effort to prevent promiscuity among adolescents in Kute Kering Village, the role and efforts of religious educators are needed. Kute Kering Village was assigned a Civil Servant Religious Counselor who was placed by the Ministry of Religion of the Regency as a mentor and religious counselor in the village in an effort to strengthen religious knowledge and knowledge as well as overcome social problems in the Islamic community, especially youth in the village, besides the PNS religious instructors there were two ( 2) non-PNS religious counselors who live in the village who also have the same role in providing religious guidance to adolescents so that adolescent religious education increases. This research method is a qualitative method, namely research that describes objective conditions in the field with research informants from village heads, religious extension workers, religious leaders and youth, research analysis is by data reduction, data presentation and drawing conclusions. The results of this study illustrate that religious instructors are making efforts to tackle promiscuity in Kute Kering Village such as promiscuity in the form of adultery, drugs, theft and rape that often occur among adolescents. The efforts made by religious educators in tackling promiscuity are carry out various religious activities in the community in general and for youth in particular, and carry out legal counseling activities in collaboration with the local police so that the community is aware of the law. influencing youth and opening up opportunities and places for promiscuity. Efforts are being made to strengthen parental supervision of association and use of social media, personal guidance from religious educators and law enforcement from the police.